Antecedents of paddy production in Kano and Jigawa states, Nigeria - Ibrahim, Datti Muhammad (2021)
Nigeria has ample of land paddy farming and a young workforce. The national average of annual paddy production is around 5,000 MT, which is lower than the actual consumption by 2,300 MT yearly. The situation is exacerbated, as it was predicted that rice demand will exceed 36,000 MT by 2050. Although, several programs were implemented such as New Rice for African Varieties (NERICA) in 2008 and the Transformation Agenda in 2012, yet, insufficient paddy production and massive youths unemployment undermine Nigeria’s food policy and ultimately hinders the achievement of Sustainable Development Goals. Thus, this study addresses food insecurity that is detrimental to Nigeria and the world in general. The low use of agricultural technologies, such as fertilizers, certified seeds and machinery, among others, was linked as the main factors causing low paddy production. Rapid population growth is also a catalyst to this situation. Thus, the Nigerian government provides farm inputs subsidies. The effect of subsidized farm technology on paddy production was investigated. The result revealed the relevance of subsidies on fertilizers, certified seeds, and tractor services. Unlike most of the previous studies that concentrated on a single farm input, this study contributes to current issues that are debated among policymakers. The findings will aid in redesigning policies that will expand access to farm subsidies in Nigeria. Although there is an increase in accessing extension connectivity (mobile phones and internet), yet, many youths remain unemployed notwithstanding the increase in the literacy rate. Hence, the study determines the influence of extension connectivity in attracting youths into paddy production. It has shown that extension connectivity may influence youths into paddy farming. Unlike previous studies that focused on influencing them into agriculture in general, this finding aids at incorporating extension connectivity as a means of encouraging youths to venture into paddy farming in Nigeria. The series of complaints by paddy farmers on their failure to access credit from financial institutions have raised a question on the issues that prevent access. The study examines the effect of major credit requirements, namely: the administrative process, guarantor, collateral, interest rate and the duration of principal repayment on access to credit. Many studies have examined collateral and interest, however, only a few analysed the administrative procedure. Therefore, finding of this study, will assist in addressing the challenges that stumble many paddy farmers to access credit from financial institutions in Nigeria. Questionnaires were administered to farmers from April 2020 to July 2020. Eighthundred- forty participants were selected through multistage sampling techniques. Binary and Ordinary Least Square methods were used to analyse the data. The results showed that an increase in subsidized fertilizer, certified seeds, tractor service, and credit access would increase paddy production by four, five, four and three times, respectively. The use of mobile phones by 1% may influence participation of youths in paddy farming by 26%. Furthermore, administrative procedures and guarantor requirements affect access to credit by two and three times, respectively. This study confirmed that subsidized farm technology will increase paddy production and extension connectivity will encourage the participation of youths in paddy production. The ease of essential credit conditions will promote the ability of farmers to access credit from financial institutions. This study recommends the re-planning of the farm subsidy distribution process, the need for greater attention in utilising extension connectivity in enlightening and educating youths and equipping paddy farmers with more skills and knowledge.